2021
DOI: 10.1111/ijpo.12875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of telephone support or short message service on body mass index, eating and screen time behaviours of children age 2 years: A 3‐arm randomized controlled trial

Abstract: Summary Background Few randomized controlled trial (RCT) interventions targeted children's early risk behaviours using telephone or short message service (SMS) support. Objective To evaluate the effectiveness of telephone or SMS early intervention focusing on mothers' behaviours starting from late pregnancy to improve BMI, and eating and screen time behaviours of children aged 2 years in comparison with the control group. Methods A 3‐arm RCT was conducted in Australia, 2017–2019. Two arms involved the interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
(140 reference statements)
0
17
0
Order By: Relevance
“…Briefly, the mothers and children were originally recruited for a trial aiming to investigate the effectiveness of early childhood obesity prevention using telephone support or text messages. The recruitment process and first 2-year outcomes of the original trial have been reported elsewhere ( 10 12 ). The study participants were recruited from four local health districts in NSW.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the mothers and children were originally recruited for a trial aiming to investigate the effectiveness of early childhood obesity prevention using telephone support or text messages. The recruitment process and first 2-year outcomes of the original trial have been reported elsewhere ( 10 12 ). The study participants were recruited from four local health districts in NSW.…”
Section: Methodsmentioning
confidence: 99%
“…For mothers randomized to the telephone and SMS groups, the interventions were delivered at nine stages between the third trimester of pregnancy and child age 24 months, corresponding to key developmental milestones of child feeding and movement. The outcomes of the CHAT trial at 12 and 24 months have been reported elsewhere [14,15]. Mothers in all groups, i.e., interventions and control, could access usual care.…”
Section: Study Importancementioning
confidence: 99%
“…At 2 years of age, 797 (69%) completed the telephone survey, [20,21] of whom 484 were excluded from this analysis due to lack of mother-reported child weight or height, 53 due to the lack of anthropometric measurement and 26 due to anthropometric measurement being completed beyond 30 days of telephone survey. In total 234 participants were included in this study (Fig.…”
Section: Study Participantsmentioning
confidence: 99%